Inovasi Pengajaran dan Pembelajaran Pendidikan Islam di Era Digital (Prosiding Keislaman dan Sains, 2025)
Islamic education is an education that is carried out deliberately and consciously to bridge Islamic knowledge and values ​​to students to achieve happiness in the world of the afterlife, the Koran and Hadith, as a source of value in every field of study and activity to give birth to a better generation, implementing the commands of Allah SWT and stay away from his prohibitions and in order not to be left behind you must follow the developments of the times that pass by. In today's digital era, a teacher must try to innovate in the teaching and learning process so that the content or learning materials can achieve the expected goals effectively and efficiently. Because teaching innovations using digital can increase learning motivation.
Keywords: Teaching Innovation; Digital Era; Islamic Education in the Digital Era